Implementation of Tempeh Fermentation Room to Optimize the Tempeh Fermentation Process Equipped with Temperature and Air Humidity Controls - Suwito, Djoko; Umaroh, Susi Tri; Kurniawan, Wahyu Dwi; Hidayatullah, Rachmad Syarifudin; Budijono, Agung Prijo (LPPM of NAROTAMA UNIVERSITY, 2024)
Abstract: The production of tempeh in Indonesia, particularly in SMEs located at Jalan Raya Sepande No.45 Sidoarjo, still faces challenges in the manual fermentation process, especially during unstable weather conditions. Suboptimal fermentation can lead to a decline in production quality. This community service activity aims to improve the quality and capacity of tempeh production through technological innovation. The method used is a participatory approach involving training, mentoring, and discussions between the proposing team and partners. The resulting solution includes the application of appropriate technology, such as a fermentation room equipped with temperature and humidity control, as well as improvements in packaging and digital marketing. The results of this activity show an increase in production quality and quantity, income, and the human resource capacity of the partners. The conclusion of this activity is that the participatory approach and technological innovation can significantly enhance production efficiency and partner welfare.